Vaillant’s Rule in Light of the Old Church Slavic Canon - Szeptyński, Rafał (Jezikoslovni zapiski, 2018)
The article deals with Vaillant’s rule, which describes the distribution of allomorphs of the Proto-Slavic comparative suffix. As indicated by an analysis of the Old Church Slavic corpus (compared to other old Slavic languages), Vladimir Dybo’s modern formulation of the rule requires certain corrections. In addition, this article develops Pavel S. Sigalov’s idea that the rule in question could also concern intransitive change-of-state verbs.